The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12951-020-00727-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic AFM detection of the oxidation-induced changes in size, stiffness, and stickiness of low-density lipoprotein

Abstract: Background Low-density lipoprotein (LDL) is an important plasma lipoprotein transporting lipids to peripheral tissues/cells. The oxidation of LDL plays critical roles in atherogenesis and its oxidized form (oxLDL) is an important risk factor of atherosclerosis. The biomechanical properties of LDL/oxLDL are closely correlated with the disease. To date, however, the oxidation-induced changes in size and biomechanical properties (stiffness and stickiness) of LDL particles are less investigated. Methods In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Low density lipoprotein (LDL) is a kind of lipoprotein particle that carries cholesterol into peripheral tissue cells and can be oxidized into oxidized LDL [ 38 , 39 ]. There are many unsaturated fatty acids (PUFAs) in the core fatty acids of LDL, accounting for about 35–70% of the total fatty acids of LDL, which are prone to self-oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Low density lipoprotein (LDL) is a kind of lipoprotein particle that carries cholesterol into peripheral tissue cells and can be oxidized into oxidized LDL [ 38 , 39 ]. There are many unsaturated fatty acids (PUFAs) in the core fatty acids of LDL, accounting for about 35–70% of the total fatty acids of LDL, which are prone to self-oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on native and oxidized LDL reported smaller particles and a reduced Young's modulus under acidic conditions compared to neutral environment (Wang et al, 2020(Wang et al, , 2021. The oxidized form of LDL (oxLDL) is a known risk factor in atherosclerosis.…”
Section:  Discussionmentioning
confidence: 99%
“…In agreement with previously published works of other groups [ 39 , 40 , 41 , 42 , 43 ], the AFM measurements of HDL particles were adapted for our Atomic Force Microscope (JPK BioAFM—NanoWizard 4, JPK, Berlin, Germany). AFM probes made of silicon nitride with a nominal spring constant of 0.25 N/m and a nominal tip radius between 5 and 8 nm (FASTSCAN-D, Bruker Nano Inc., Camarillo, CA, USA) were used.…”
Section: Methodsmentioning
confidence: 99%